PENERAPAN DOKTRIN BUSINESS JUDGMENT RULE TERHADAP DIREKSI ANAK PERUSAHAAN BUMN (Studi Kasus : Putusan Mahkamah Agung Nomor 121 K/Pid.Sus/2020) - Widyantoro Haryo Tetuko; Richard Candra Adam (Fakultas Hukum Universitas Tarumanagara, 2022)
The business judgment rule doctrine becomes the protector of the director of a Limited Liability Company (PT) to take actions that affect companies whose elements are regulated in Article 97 paragraph (5) of Law Number 40 of 2007. Decision Number 121 K/Pid.Sus/2020 there are differences in the views of the first and second level courts in deciding the case of Defendant KA and other directors, the Supreme Court stated that this action was a business decision that must be protected this doctrine, this shows das sollen and das sein which need to be discussed in this study.The objectives of this study are: (1) How is the application of the business judgment rule in relation to the corporate actions of directors of BUMN subsidiaries; (2) How is the application of the business judgment rule doctrine in legal considerations in relation to the Supreme Court's Cassation Decision Number 121 K/Pid.Sus/2020. Based on the research results it is known: (1) The application of the business judgment rule doctrine to the actions of the directors of a BUMN subsidiary in BMG Australia transactions fulfills all the elements of the doctrine; (2) The application of the business judgment rule doctrine in the a quo has applied the business judgment rule doctrine from its considerations which state that the KA and other Company Directors develop the company by means of increasing oil and gas reserves so that it is protected by this doctrine as stipulated in Article 97 paragraph (5) of the Company Law .